2015
DOI: 10.1038/nrcardio.2015.161
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve disease—morphology and mechanisms

Abstract: Mitral valve disease is a frequent cause of heart failure and death. Emerging evidence indicates that the mitral valve is not a passive structure, but—even in adult life—remains dynamic and accessible for treatment. This concept motivates efforts to reduce the clinical progression of mitral valve disease through early detection and modification of underlying mechanisms. Discoveries of genetic mutations causing mitral valve elongation and prolapse have revealed that growth factor signalling and cell migration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
254
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(301 citation statements)
references
References 307 publications
(399 reference statements)
9
254
0
7
Order By: Relevance
“…Mitral valve regurgitation (MR) is one of the most common valvular diseases worldwide and leads to heart failure and other potentially severe complications 1. Since there is still a high rate of patients with an indication for mitral valve repair, who cannot receive surgical repair because of an increased perioperative risk,2 percutaneous edge‐to‐edge mitral valve reconstruction (PMVR) using the MitraClip system (Abbott Vascular) has become a safe and viable alternative to treat severe mitral regurgitation in these patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…Mitral valve regurgitation (MR) is one of the most common valvular diseases worldwide and leads to heart failure and other potentially severe complications 1. Since there is still a high rate of patients with an indication for mitral valve repair, who cannot receive surgical repair because of an increased perioperative risk,2 percutaneous edge‐to‐edge mitral valve reconstruction (PMVR) using the MitraClip system (Abbott Vascular) has become a safe and viable alternative to treat severe mitral regurgitation in these patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is emerging that degenerative MVDs are the result of modified adult valve biology [4,5]. Particularly, Levine and colleagues have recently underlined that MVDs are the result of a 'living valve', which with advancing age shows active changes mediated both by valvular endothelial and interstitial cells and alterations in composition and turnover of elements of extracellular matrix [6]. Accordingly, in surgically excised human myxomatous tissues, an overexpression of transforming growth factor-β cytokine (TGF-β) pathway, an increased release of metalloproteinases (MMPs), and down-expression of related inhibitors (TIMPs), responsible for degeneration of collagen and elastin structures, have been observed [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In hypertrophic cardiomyopathy (HCM), the leaflet elongation exceeds the needs of the reduced volume of the LV, further aggravating the left ventricular outflow tract (LVOT) obstruction and can predispose to systolic anterior motion (SAM) of the MV. 5,7 In MVP, the leaflets are long and exhibit structural fibroelastic abnormalities. 5,8 The surgical treatment has an important role in the natural history of the disease and it has been proven to be the only treatment that may efficiently prevent heart failure, improving symptoms and reducing mortality by 70%.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that it can react to the morphological changes that involve the LV and that it may also alter its structure irrespective of the state of the nearby structures. 5,6 However, concurrent with ventricular remodeling, mitral leaflets can become inadequately small (as seen in dilated cardiomyopathies) or suffer a process of elongation. In hypertrophic cardiomyopathy (HCM), the leaflet elongation exceeds the needs of the reduced volume of the LV, further aggravating the left ventricular outflow tract (LVOT) obstruction and can predispose to systolic anterior motion (SAM) of the MV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation